Aminomethylation of Enals through Carbene and Acid Cooperative Catalysis: Concise Access to β2‐Amino Acids1. Issue 17 (3rd March 2015) - Xu, Jianfeng; Chen, Xingkuan; Wang, Ming; Zheng, Pengcheng; Song, Bao‐An; Chi, Yonggui Robin
Abstract A convergent, organocatalytic asymmetric aminomethylation of α, β‐unsaturated aldehydes by N‐heterocyclic carbene (NHC) and (in situ generated) Brønsted acid cooperative catalysis is disclosed. The catalytically generated conjugated acid from the base plays dual roles in promoting the formation of azolium enolate intermediate, formaldehyde‐derived iminium ion (as an electrophilic reactant), and methanol (as a nucleophilic reactant). This redox‐neutral strategy is suitable for the scalable synthesis of enantiomerically enriched β2‐amino acids bearing various substituents.